Exploring the relationship between mental health, safety climate and job satisfaction among physiotherapists in Klang Valley - Nur Syahirah, Mohamad Rosli (2023)
In the high-stress world of healthcare, the intertwined relationship between mental health, safety climate and job satisfaction are pivotal. Prioritizing healthcare professionals’ mental health and nurturing a positive safety climate are essential to enhancing overall job satisfaction. This study aimed to investigate the relationship between mental health, safety climate and job satisfaction among physiotherapists in Klang Valley and to elucidate the effect of demographic variables on these elements. The findings of this study intend to offer valuable insights into potential strategies that healthcare organizations and policymakers may implement to elevate job satisfaction and increase overall productivity. A sample of 200 physiotherapists, encompassing a diverse range of demographic backgrounds, took part in this investigation. Data analysis was conducted using Pearson Correlation Analysis, One-Way ANOVA and Multiple Regression Analysis to determine the relationships among mental health, safety climate, and job satisfaction, and to identify the influence of various demographic characteristics on job satisfaction. The findings revealed a moderate positive correlation between mental health and job satisfaction, and a robust correlation between safety climate and job satisfaction. Interestingly, demographics such as age, gender, education level, years of experience, and work setting demonstrated no significant different on job satisfaction. The combined effect of mental health and safety climate accounted for 67.4% of the variance in job satisfaction. Further analysis determined that safety climate significantly predicts job satisfaction, whereas mental health lacked statistical significance. The research highlights the importance of prioritizing employees' mental health and safety to enhance job satisfaction and reduce turnover. It proposes comprehensive training and safety policies, emphasizing the role of policymakers in implementing regulations for workplace improvement.